COVID-19 Infection in Pregnancy: A Review - Mily, Sabrina J.; Akter, Kazi Mahmuda; Jabin, Nowshin; Mitra, Saikat; Emran, Talha Bin; Nandi, Monisha; Baral, Sumit Kumar; Uddin, Md. Zia; Mallick, Jewel; Paul, Arkajyoti; Shah, Syed U. A.; Rauf, Abdur; et al. (Infectious Disorders - Drug Targets, 2022)
Coronavirus disease 2019 (COVID-19), which is a highly contagious viral illness caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has had a catastrophic effect on the world's demographics, resulting in more than 3.8 million deaths worldwide and establishing itself as the most serious global health crisis since the 1918 influenza pandemic. Several questions remain unanswered regarding the effects of COVID-19 disease during pregnancy. Although most infections are mild in high-risk populations, the severe disease frequently leads to intubation, intensive care unit admission, and, in some cases, death. Hormonal and physiological changes in the immune and respiratory systems, cardiovascular function, and coagulation may affect the progression of COVID-19 disease in pregnancy. However, the consequences of coronavirus infection on implantation, fetal growth and development, labor, and newborn health have yet to be determined, and, consequently, a coordinated global effort is needed in this respect. Principles of management concerning COVID-19 in pregnancy include early isolation, aggressive infection control procedures, oxygen therapy, avoidance of fluid overload, consideration of empiric antibiotics (secondary to bacterial infection risk), laboratory testing for the virus and co-infection, fetal and uterine contraction monitoring, prevention, and / or treatment of thromboembolism early mechanical ventilation for progressive respiratory failure, individualized delivery planning, and a team-based approach with multispecialty consultations. This review focuses on COVID-19 during pregnancy, its management, and the area where further investigations are needed to reduce the risk to mothers and their newborns.
Keywords: pregnancy